Short and prolonged maternal separation impacts on ethanol-related behaviors in rats: sex and age differences - Leichtweis, Kamila Souto; Carvalho, Marielly; Morais-Silva, Gessynger [UNESP]; Marin, Marcelo Tadeu [UNESP]; Amaral, Vanessa Cristiane Santana (Taylor & Francis, 2019)
Maternal separation (MS) is an animal model widely used to evaluate the influence of early-life stress exposure on ethanol consumption and dependence. The goal of this study was to evaluate the effects of brief and prolonged MS on the pattern of consumption and ethanol conditioned place preference (CPP) in male and female rats during adolescence and adulthood. Wistar rat pups were separated daily from their dams for 15 or 180 minutes during the 2 to 10 postnatal days (PND). In adolescence, half of the litter from each group was evaluated in the ethanol consumption test using the three-bottle test choice paradigm. In addition, using biased procedure, ethanol-conditioned place preference was also evaluated. In adulthood, the other half of the litter was evaluated on the same tests. Our results showed that there are differences in consumption pattern and in alcohol reinforcement between males and females, adolescents and adults. While prolonged MS had no effect on total ethanol consumption in adolescents of both sexes, it induced CPP in these animals. In turn, in adults, previous exposure to prolonged MS increased ethanol consumption without altering ethanol-CPP.Lay summary Giving the importance of the mother-children (dam-pups when talking about rodents) relationship to proper brain development, the separation of pups from their dam is broadly used as an animal model to study the impact of early-life stress exposure. Here, we used a protocol of brief or prolonged maternal separation to study the impact of early-life stress exposure in the alcohol consumption and conditioned place preference in rats, and how age and sex influence it. We showed that, overall, the prolonged maternal separation increased alcohol consumption in both males and females, but only when animals were tested during the adulthood. In the other hand, prolonged maternal separation increased ethanol conditioned place preference in adolescent rats, both male and female.
Keywords: adolescents; adults; conditioned place preference; dependence; Early-life stress; free-choice ethanol consumption